Neither Bereavement nor Grief: Coping with the Death of a Cherished Person in the "Cunda-sutta" - Tsai, Yao-ming (Contemporary buddhism, 2016)
Though bereavement and grief have been common human experience throughout recorded history, how bereavement is viewed and grief coped with varies from one philosophical tradition to another. By examining features running throughout the Cunda-sutta, this paper demonstrates a shift from the ordinary conception of bereavement to an insightful understanding of not-bereavement. If one possesses insight into how worldly convention shapes ordinary conceptions of bereavement, then one need not associate bereavement with loss and grief. For ordinary people, grief may be regarded as a natural response to loss. However, in light of the emptiness of bereavement, the emphasis can be shifted from coping with grief to the understanding of not-grief and to the cultivation of mental abilities conducive to moving forward on the right path. By examining the reasoning of neither bereavement nor grief, this paper sheds new light on a rarely acknowledged perspective on coping with the death of a cherished person.